Kepler-20: a sun-like star with three sub-neptune exoplanets and two earth-size candidates - Gautier, Thomas N.; Charbonneau, David; Rowe, Jason F.; Marcy, Geoffrey W.; Isaacson, Howard; Torres, Guillermo; Fressin, Francois; Rogers, Leslie A.; Désert, Jean-Michel; Buchhave, Lars A.; Latham, David W.; Quinn, Samuel N.; et al. (The Astrophysical Journal, 2012)
We present the discovery of the Kepler-20 planetary system, which we initially identified through the detection of five distinct periodic transit signals in the Kepler light curve of the host star 2MASS J19104752+4220194. From high-resolution spectroscopy of the star, we find a stellar effective temperature T eff = 5455 100 K, a metallicity of [Fe/H] = 0.01 0.04, and a surface gravity of log g = 4.4 0.1. We combine these estimates with an estimate of the stellar density derived from the transit light curves to deduce a stellar mass of M = 0.912 0.034 M and a stellar radius of R = 0.944 +0.060 -0.095 R. For three of the transit signals, we demonstrate that our results strongly disfavor the possibility that these result from astrophysical false positives. We accomplish this by first identifying the subset of stellar blends that reproduce the precise shape of the light curve and then using the constraints on the presence of additional stars from high angular resolution imaging, photometric colors, and the absence of a secondary component in our spectroscopic observations. We conclude that the planetary scenario is more likely than that of an astrophysical false positive by a factor of 2 × 105 (Kepler-20b), 1 × 105 (Kepler-20c), and 1.1 × 103 (Kepler-20d), sufficient to validate these objects as planetary companions. For Kepler-20c and Kepler-20d, the blend scenario is independently disfavored by the achromaticity of the transit: from Spitzer data gathered at 4.5 μm, we infer a ratio of the planetary to stellar radii of 0.075 0.015 (Kepler-20c) and 0.065 0.011 (Kepler-20d), consistent with each of the depths measured in the Kepler optical bandpass. We determine the orbital periods and physical radii of the three confirmed planets to be 3.70days and 1.91+0.12 -0.21 R ⊕ for Kepler-20b, 10.85days and 3.07+0.20 -0.31 R ⊕ for Kepler-20c, and 77.61days and 2.75+0.17 -0.30 R ⊕ for Kepler-20d. From multi-epoch radial velocities, we determine the masses of Kepler-20b and Kepler-20c to be 8.7 2.2 M ⊕ and 16.1 3.5 M ⊕, respectively, and we place an upper limit on the mass of Kepler-20d of 20.1 M ⊕ (2σ). © 2012 The American Astronomical Society. All rights reserved.
Keywords: dept.phy; eclipses; planetary systems

Kepler-14b: A Massive Hot Jupiter Transiting an F Star in a Close Visual Binary - Buchhave, Lars A; Latham, David W; Carter, Joshua A; Desert, J M; Torres, Guillermo; Adams, Elisabeth R; Bryson, Stephen T; Charbonneau, David; Ciardi, David R; Kulesa, Craig; Dupree, Andrea K; Fischer, Debra A; et al. (Astrophysical Journal Supplement Series, 2011)
We present the discovery of a hot Jupiter transiting an F star in a close visual (03 sky projected angular separation) binary system. The dilution of the host star's light by the nearly equalmagnitude stellar companion (∼0.5mag fainter) significantly affects the derived planetary parameters, and if left uncorrected, leads to an underestimate of the radius and mass of the planet by 10% and 60%, respectively. Other published exoplanets, which have not been observed with high-resolution imaging, could similarly have unresolved stellar companions and thus have incorrectly derived planetary parameters. Kepler-14b (KOI-98) has a period of P = 6.790 days and, correcting for the dilution, has a mass of Mp = 8.40+0.35 -0.34 M J and a radius of Rp = 1.136+0.073-0.054 R J, yielding a mean density of ρp = 7.1 ± 1.1 g cm-3. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (Kepler-14b, KIC 10264660, 2MASS J19105011+4719589); techniques: photometric; techniques: spectroscopic

Characteristics of kepler planetary candidates based on the first data set - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Boss, Alan P.; Brown, Timothy M.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Dupree, Andrea K.; et al. (The Astrophysical Journal, 2011)
In the spring of 2009, the Kepler Mission commenced high-precision photometry on nearly 156,000 stars to determine the frequency and characteristics of small exoplanets, conduct a guest observer program, and obtain asteroseismic data on a wide variety of stars. On 2010 June 15, the Kepler Mission released most of the data from the first quarter of observations. At the time of this data release, 705 stars from this first data set have exoplanet candidates with sizes from as small as that of Earth to larger than that of Jupiter. Here we give the identity and characteristics of 305 released stars with planetary candidates. Data for the remaining 400 stars with planetary candidates will be released in 2011 February. More than half the candidates on the released list have radii less than half that of Jupiter. Five candidates are present in and near the habitable zone; two near super-Earth size, and three bracketing the size of Jupiter. The released stars also include five possible multi-planet systems. One of these has two Neptune-size (2.3 and 2.5 Earth radius) candidates with near-resonant periods. © 2011. The American Astronomical Society.
Keywords: Planets and satellites: detection; Surveys; dept.phy

Characteristics of planetary candidates observed by Kepler II : Analysis of the first four months of data - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Brown, Timothy M.; Bryson, Stephen T.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2011)
On 2011 February 1 the Kepler mission released data for 156,453 stars observed from the beginning of the science observations on 2009 May 2 through September 16. There are 1235 planetary candidates with transit-like signatures detected in this period. These are associated with 997 host stars. Distributions of the characteristics of the planetary candidates are separated into five class sizes: 68 candidates of approximately Earth-size (Rp < 1.25 R⊕), 288 super-Earth-size (1.25 R⊕ ≤ R p < 2 R⊕), 662 Neptune-size (2 R ⊕ ≤ Rp < 6 R⊕), 165 Jupiter-size (6 R⊕ ≤ Rp < 15 R ⊕), and 19 up to twice the size of Jupiter (15 R ⊕ ≤ Rp < 22 R⊕). In the temperature range appropriate for the habitable zone, 54 candidates are found with sizes ranging from Earth-size to larger than that of Jupiter. Six are less than twice the size of the Earth. Over 74% of the planetary candidates are smaller than Neptune. The observed number versus size distribution of planetary candidates increases to a peak at two to three times the Earth-size and then declines inversely proportional to the area of the candidate. Our current best estimates of the intrinsic frequencies of planetary candidates, after correcting for geometric and sensitivity biases, are 5% for Earth-size candidates, 8% for super-Earth-size candidates, 18% for Neptune-size candidates, 2% for Jupiter-size candidates, and 0.1% for very large candidates; a total of 0.34 candidates per star. Multi-candidate, transiting systems are frequent; 17% of the host stars have multi-candidate systems, and 34% of all the candidates are part of multi-candidate systems. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; planets and satellites: detection; stars: statistics; surveys

Kepler-22b: A 2.4 Earth-radius Planet in the Habitable Zone of a Sun-like Star - Borucki, William J.; Koch, David G.; Batalha, Natalie M.; Bryson, Stephen T.; Rowe, Jason F.; Fressin, Francois; Torres, Guillermo; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2012)
A search of the time-series photometry from NASA's Kepler spacecraft reveals a transiting planet candidate orbiting the 11th magnitude G5 dwarf KIC 10593626 with a period of 290 days. The characteristics of the host star are well constrained by high-resolution spectroscopy combined with an asteroseismic analysis of the Kepler photometry, leading to an estimated mass and radius of 0.970 0.060 M and 0.979 0.020 R. The depth of 492 10 ppm for the three observed transits yields a radius of 2.38 0.13 Re for the planet. The system passes a battery of tests for false positives, including reconnaissance spectroscopy, high-resolution imaging, and centroid motion. A full BLENDER analysis provides further validation of the planet interpretation by showing that contamination of the target by an eclipsing system would rarely mimic the observed shape of the transits. The final validation of the planet is provided by 16 radial velocities (RVs) obtained with the High Resolution Echelle Spectrometer on Keck I over a one-year span. Although the velocities do not lead to a reliable orbit and mass determination, they are able to constrain the mass to a 3σ upper limit of 124 M ⊕, safely in the regime of planetary masses, thus earning the designation Kepler-22b. The radiative equilibrium temperature is 262 K for a planet in Kepler-22b's orbit. Although there is no evidence that Kepler-22b is a rocky planet, it is the first confirmed planet with a measured radius to orbit in the habitable zone of any star other than the Sun. © 2012. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: fundamental parameters; stars: individual (Kepler-22, KIC 10593626)